Correlation between Coral Reef Cover Condition and the Abundance of Megabenthos on Setan Island, West Sumatra - Siringoringo, Frido S.; Mulyadi, Aras; Thamrin, Thamrin (Journal of Coastal and Ocean Sciences, 2024)
In the coral reef ecosystem, there is a food source for small fish, which are prey for various kinds of associated biota; one of the biota that lives in the coral reef ecosystem is megabenthos. Megabenthos is influenced by the quality of the coral reef ecosystem, where if conditions are good, the coral will have a greater chance of high megabenthos diversity. This research was carried out in March 2023 in Setan Island, West Sumatra. This research analyzes the relationship between coral reef conditions and megabenthos abundance. The method used in this research is a survey method. Observations of coral reef cover were carried out using the Underwater Photo Transect (UPT) method, and megabenthos abundance was measured using the Benthos Belt Transect (BBT) method. Observations were carried out at four stations (3 and 6 m deep) with a transect length of 50 m. Based on the average value of the percentage of coral reef cover, it is still categorized as being in poor condition, namely 18.87%. There is a relationship between the percentage of live coral reef cover and the abundance of megabenthos with a percentage of 55.27%, with the types of megabenthos clams (Tridacna sp), sea cucumbers (Holothuria sp), snails (Trochus sp), lobsters (Panulirus sp), fur pigs (Diadema sp), snails (Drupella sp), and starfish (Acanthasper sp).